Harmonisasi Hukum dan Penegakan Hukum yang Berkeadilan dalam Tindak Pidana Judi Togel dan Online - Mutabar, Salnaf Faqih (Proceedings Series on Social Sciences & Humanities, 2024)
Gambling and online gambling have become a disturbing phenomenon in society. This gambling not only has a negative impact on individuals, but also on society as a whole. The purpose of this article is so that people who are still actively gambling can stop and law enforcers can further improve prevention and restore disturbances. The method used is juridical-sociological which not only focuses on written law but considers social aspects. Crime prevention efforts are actually a continuous and continuous effort. There is no, and there will never be a final effort. However, efforts must still be made to further ensure the protection and welfare of society. However, efforts must still be made to further ensure the protection and welfare of society. Suggestions for law enforcers are to carry out strict supervision, take firm action and provide rehabilitation for gambling addicts.